1998
DOI: 10.1016/s0014-5793(98)01505-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid hyaluronan uptake is associated with enhanced motility: implications for an intracellular mode of action

Abstract: Texas red-labeled hyaluronan (TR-HA) is rapidly taken up in a CD44 independent manner into ras-transformed 10T1/2 fibroblasts, where it accumulates in both cell ruffles/ lamellae, the perinuclear area, and the nucleus. HA does not accumulate in the cell ruffles/lamellae of parental 10T1/2 cells. Addition of HA to ras-transformed cells promotes their random motility but has no effect on 10T1/2 cell motility. 10T1/2 cells can be modified to take up HA into cell ruffles by exposure to phorbol ester or direct micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 46 publications
4
76
0
Order By: Relevance
“…It has also been suggested that both extracellular and intracellular HA have crucial roles in cell motility via interaction with cell surface receptors such as CD44, RHAMM and ICAM-1, and rapid uptake of exogenously added HA [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that both extracellular and intracellular HA have crucial roles in cell motility via interaction with cell surface receptors such as CD44, RHAMM and ICAM-1, and rapid uptake of exogenously added HA [31].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard it is noteworthy that internalization into endothelial cells of a complex of heparan sulfate-proteoglycan and a heparin-binding protein targets the latter to mitochondria, consequently preventing apoptosis (40). Also, as mentioned above, exogenously added hyaluronan can be targeted to various intracellular compartments and results in increased cell motility (13). Interestingly, targeting of hyaluronan to the nucleus was blocked by (R/K)X 7 (R/K)-containing peptide in the latter study, suggesting the possible involvement of an IHABP.…”
Section: Discussionmentioning
confidence: 98%
“…Does intracellular hyaluronan, like extracellular hyaluronan, play an important role in regulating cellular behavior through interactions with IHABPs? Recently, it was reported that rapid uptake of Texas red-labeled hyaluronan and its subsequent accumulation in the cell processes, perinuclear area, and nucleus of transformed cells were associated with enhanced cell motility (13). Furthermore, careful examination confirmed the intracellular localization of endogenous hyaluronan as well as hyaluronan-binding sites and demonstrated dynamic changes in their pattern of distribution during proliferation of smooth muscle cells and fibroblasts (8).…”
Section: Hyaluronan Is a Ubiquitous Glycosaminoglycan (Gag)mentioning
confidence: 89%
See 1 more Smart Citation
“…HA is involved in numerous important processes such as water homeostasis of tissues and joint lubrication [1], cartilage matrix stabilization [4,1], cell motility [5,6], morphogenesis and embryogenesis [7], and inflammation [8].…”
Section: Introductionmentioning
confidence: 99%